Minimizing variation order on construction project due to design change - Hamdan, Hazrin (2012)
There are several issues frequently exist in the process of project implementation in Malaysia. Those issues typically affect the project performance through the occurrence of variation order during the construction phase and resulting in cost overrun and delays in project completion. Nowadays variation orders become a common phenomenon in our construction industry. Construction projects process known to be complex activities due to critical involvement of many human and non-human factors, time factor, high variability, various uncertainties and also complex relationships among the participants. In some cases, the issues on variation order become worst if both parties i.e. client and contractor have a conflict of understanding which leads to contract disputes and the project might end-up with arbitration, litigation or total abandonment. The objective of this research is to identify the causes of variation order in the construction project. The focus is on the causes which led to the weaknesses of implementation at the pre-construction stage. Further, the impacts to the project performance shall be determined and followed by the strategies to minimize the variation orders. The study process involved the literature review, gathering information from journals, questionnaires survey, analysis, conclusion and recommendation. Relative Importance Index (I) technique analysis is used to rank the identified factors. Based on the above analysis, the results shows that the most significant causes of variation order are design faulty/wrong technical data; duration for design phase too short; and communication breakdown & lack of coordination among consultants. For the most significant impact, the result shows that late completion (extension of time) and cost overrun were the highest rating. While the strategies for minimizing the variation orders based on highest rating was to select the competent & experience consultant company; and also appointment of experience and competent designer.